Vertical strain partitioning in hot Variscan crust: Syn-convergence escape of the Pyrenees in the Iberian-Armorican syntax - Cochelin Bryan (BSGF - Earth Sciences Bulletin, 2017)
A new structural map of the Paleozoic crust of the Pyrenees based on an extensive compilation and new kinematic data allows for the evaluation of the mechanical coupling between the upper and lower crust of the abnormally hot foreland of the Variscan orogen of SW Europe. We document partitioning between coeval lower crustal lateral flow and upper crustal thickening between 310 and 290 Ma under an overall dextral transpressive regime. Partitioning also involved syn-convergence transtensional gneiss domes emplacement during this period. Late orogen-normal shortening of the domes and strain localization in steep crustal-scale transpressive shear zones reflects increasing coupling between the lower crust and the upper crust. The combination of dextral transpression and eastward flow in the Pyrenees results from the shortening and lateral escape of a hot buoyant crust along the inner northern limb of the closing Cantabrian orocline at the core of the Iberian-Armorican arc between ca. 305 and 295 Ma. Delamination or thermal erosion of the lithosphere enhanced orocline closure and explains (1) the switch from crust- to mantle-derived magmatism in the Iberian-Armorican arc and (2) the abnormally hot and soft character of the Pyrenean crust that escaped the closing syntax.